Homopropargyl alcohol 5,5-diphenylpent-2-yne-1,5-diol - Umaña, Christian A. (2018)
In the title compound, C17H16O2, the central carbon atom has a distorted tetrahedral geometry [spread of angles = 105.71 (8)–112.75 (9)°] for its bonds to a homopropargylic but-2-yn-1-ol moiety, a hydroxy group and two phenyl substituents. In the crystal, O—H⋯O hydrogen-bonding interactions link the molecules into [001] chains and C—H⋯π(ring) contacts consolidate the packing.